SPIRAL2 Cryomodule Models: A Gateway to Process Control and Machine Learning - Vassal, Adrien; Ghribi, Adnan; Millet, François; Bonne, François; Bonnay, Patrick; Bernaudin, Pierre-Emmanuel (Frontiers in Physics, 2022)
From simple physical systems to full production lines, numerical models could be used to minimize downtime and to optimize performances. In this article, the system of interest is the SPIRAL2 heavy ions accelerator cryogenic system. This paper illustrates three different applications based on a SPIRAL2 cryostat model: optimal controller synthesis, virtual sensor synthesis and anomaly detection. The two first applications have been deployed on the system. Experimental results are used to illustrate the benefits of such applications. The third application is a case study based on data generated from a thermodynamic twin model.